PROBLEMATIKA EPISTEMOLOGIS TENTANG VISI, MISI, DAN TUJUAN PENDIDIKAN ISLAM - Rijal, Syamsul (Fakultas Agama Islam Universitas Islam Madura, 2019)
The hegemonic challenges of Western globalization have caused serious impacts on the future of Islamic education. This reality must be realized by Muslims and more specifically those involved in the world of education. For this reason, there is an anticipatory and alternative tactical and strategic step to free themselves from the hegemonic grip of Western globalization. The conception of Islamic model education does not only see education as an attempt to